2002
DOI: 10.1038/sj.bdj.4801653
|View full text |Cite
|
Sign up to set email alerts
|

The nature and quality of periodontal related patient information on the world-wide web

Abstract: Background The internet provides a potentially invaluable source of health education material for members of the public. Objectives This study aimed to investigate the nature and quality of periodontal-related patient information on the world-wide web. Methods The search term ' "gum disease" AND "patient information" ' was entered into three common internet search engines. The top 50 sites identified by each search engine were downloaded and assessed for authorship, content, accord with accepted dental practic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 7 publications
0
18
0
Order By: Relevance
“…To the best of our knowledge, studies investigating Web‐based information on oral medicine and dentistry have been so far scarce and dealt with either head and neck cancer (López‐Jornet and Camacho‐Alonso, ; Ni Riordain and McCreary, ) leukoplakia (López‐Jornet and Camacho‐Alonso, ), orthodontic treatment (Jiang, ; Antonarakis and Kiliaridis, ; Patel and Cobourne, ; Aldairy et al , ; Livas et al , ) temporomandibular disorders (Türp et al , ; Park et al , ), mouth guards (Magunacelaya and Glendor, ), or periodontal diseases (Chestnutt, ). A wide variety of validation tools has been used in the aforementioned studies, for example JAMA benchmarks, DISCERN, HON seal, LIDA, FRES, Flesch‐Kinkaid Grade Level, Fog Scale Level, as well as personal scoring systems, making it difficult to compare the results and thus draw specific conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, studies investigating Web‐based information on oral medicine and dentistry have been so far scarce and dealt with either head and neck cancer (López‐Jornet and Camacho‐Alonso, ; Ni Riordain and McCreary, ) leukoplakia (López‐Jornet and Camacho‐Alonso, ), orthodontic treatment (Jiang, ; Antonarakis and Kiliaridis, ; Patel and Cobourne, ; Aldairy et al , ; Livas et al , ) temporomandibular disorders (Türp et al , ; Park et al , ), mouth guards (Magunacelaya and Glendor, ), or periodontal diseases (Chestnutt, ). A wide variety of validation tools has been used in the aforementioned studies, for example JAMA benchmarks, DISCERN, HON seal, LIDA, FRES, Flesch‐Kinkaid Grade Level, Fog Scale Level, as well as personal scoring systems, making it difficult to compare the results and thus draw specific conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…8,14 This was reinforced by some respondents having difficulties finding information for their own use or having discovered information, being sufficiently concerned about its accuracy, to be discouraged from referring patients to the Internet. However, despite these reservations, 40.4% agreed or strongly agreed that the Internet was a useful source of information for patients.…”
Section: Discussionmentioning
confidence: 99%
“…7 The first study of dental information for patients on the Internet concluded that judicious and active support from professionals would be required to aid patients' interpretation of periodontal-related patient information sites. 8 It has also recently been shown that a good deal of the Internet derived information on common oral pathologies is beyond the average UK reading age. 9 As the NHS develops its information technology strategy in relation to dentistry, information is required on how best to harness the undoubted benefits of the Internet, to improve the delivery of dental care and facilitate the promotion of oral health.…”
Section: Introductionmentioning
confidence: 99%
“…It is interesting that the majority of patients who sought oral health information found the information useful. However, the information jungle that is the Internet, implies that patients need judicious guidance in sorting useful from less useful information (8), and dental hygienists must be prepared to discuss issues raised by patients concerning information they obtained on‐line. In addition, it is the duty of oral health professions to appreciate the knowledge base of their patients.…”
Section: Discussionmentioning
confidence: 99%
“…While there is a considerable body of research on the impact of the Internet‐based patient education material as it relates to medicine in general (6), the implications for dental care are unknown (7). The first study of the quality of dental information for patients on the Internet concluded that judicious and active support from professionals would be required to aid patients’ interpretation of periodontal‐related patient information sites (8). In mid‐2004, 61% of the adult population in the UK, claimed to have accessed the Internet (9).…”
Section: Introductionmentioning
confidence: 99%